Scent of a woman - Pacino, Al, 1940-; O'Donnell, Chris; Brest, Martin (Universal Home Video, 1993)
Hoping to earn extra money, an innocent and reserved scholarship student at an exclusive prep school agrees to look after a blind, retired Lieutenant Colonel, who takes him off for a wild weekend in New York City.